2021
DOI: 10.1002/ange.202111829
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Imaging of Mitochondrial DNA Base Excision Repair Reveals Dynamics of Oxidative Stress Responses

Abstract: Mitochondrial function in cells declines with aging and with neurodegeneration, due in large part to accumulated mutations in mitochondrial DNA (mtDNA) that arise from deficient DNA repair. However, measuring this repair activity is challenging. We employ a molecular approach for visualizing mitochondrial base excision repair (BER) activity in situ by use of a fluorescent probe (UBER) that reacts rapidly with AP sites resulting from BER activity. Administering the probe to cultured cells revealed signals that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…In the brain, no significant differences in OG accumulation have been found in Ogg1, Mutyh and DKO mice (3,34). To our knowledge, no other study has quantified OG in DNA glycosylase deficient HAP1 cells, however, one study analyzed repair capacity and found that OGG1 deficient HAP1 cells showed a higher rate of BER than WT cells at baseline (35) suggesting efficient compensation of other available DNA glycosylases in the absence of OGG1. A potential candidate is Nth-like DNA glycosylase 1 (NTHL1) that was shown to repair OG (36) and is also expressed at high levels in HAP1 cells (31).…”
Section: Discussionmentioning
confidence: 99%
“…In the brain, no significant differences in OG accumulation have been found in Ogg1, Mutyh and DKO mice (3,34). To our knowledge, no other study has quantified OG in DNA glycosylase deficient HAP1 cells, however, one study analyzed repair capacity and found that OGG1 deficient HAP1 cells showed a higher rate of BER than WT cells at baseline (35) suggesting efficient compensation of other available DNA glycosylases in the absence of OGG1. A potential candidate is Nth-like DNA glycosylase 1 (NTHL1) that was shown to repair OG (36) and is also expressed at high levels in HAP1 cells (31).…”
Section: Discussionmentioning
confidence: 99%
“…Following exposure of the cells to an exogenous oxidating compound, mitochondrial BER was greatly elevated in the MTH1 KO cell line demonstrating the importance of sanitizing 8-oxoG precursors in mitochondria. The OGG1 KO cells showed lower BER activity than both MTH1 KO cells and the wild-type control cells resulting in the accumulation of 8-oxoG lesions in mtDNA (Jun et al, 2022).…”
Section: Disconnection Of Mtdna Damage and Mtdna Mutation Loadmentioning
confidence: 86%
“…Thus, despite recent reports showing that BER deficiency does not lead to increased mutation load in mtDNA or mtRNA in mice (Kauppila et al, 2018), the fact that BER, as well as the nucleotide pool sanitizing enzymes MTH1 and deoxyuridine nucleotidohydrolase (dUTPase) that eliminates dUTP, exist in mitochondria indicate the importance of preventing and repairing base lesions in mtDNA (Kang et al, 1995;Ladner and Caradonna, 1997;Ichikawa et al, 2008;Jun et al, 2022).…”
Section: Disconnection Of Mtdna Damage and Mtdna Mutation Loadmentioning
confidence: 98%
See 1 more Smart Citation
“…Mitochondrial transcription factor A (TFAM), which is located in mitochondria, is necessary for mtDNA replication and mitochondrial biogenesis [9]. However, mtDNA lacks a mature self-repair system and is susceptible to mutations triggered by external disturbances [10]. mtDNA damage leads to cellular dysfunction and disease occurrence [11,12].…”
Section: Ivyspring International Publishermentioning
confidence: 99%